Implicit Voice Delivery: Its Antecedents, Consequences, and Boundary Conditions. (February 2022) - Ren, Run; Ma, Li; Chen, (George) Zhen Xiong; Wang, Hui; Ju, Dong
ABSTRACT: Although many organizations encourage employees to voice, employees may be reluctant to voice directly because they are afraid that their supervisors will perceive it as challenging their face (i.e., the positive image or social value of an individual). Alternatively, employees could deliver improvements or express concerns to their supervisors using indirect and implicit approaches, which we refer to as 'implicit voice delivery'. Applying face theory, we examine the antecedents and outcomes as well as two boundary conditions of implicit voice delivery in organizations with two studies. In Study 1, we define the construct and develop a measure of implicit voice delivery. In Study 2, we test our proposed model with supervisor-subordinate dyadic data from a time-lagged survey. Results demonstrate that concern for other people's face drives employees to express their voices implicitly and that this relationship is stronger when supervisors' concern for their own face is high rather than low. In addition, implicit voice delivery is associated with supervisors' favorable response in terms of voice endorsement. Furthermore, the effect on voice endorsement is stronger when the supervisor is more able to infer meaning from implicit messages. Theoretical contribution and managerial implications are discussed. 摘要: 在管理战略变革时，决策制定者不可避免地面临各种各样的张力。以往在组织战略视角下做的研究，如悖论与组织学习，对决策制定的系统性心智模式和思维过程提供的见解有用但相当局限。本文援引超悖论视角的理论与哲学基础以及其它相应理论，构建了决策制定的超悖论动态循环过程模型。这一模型由三个互相关联的维度构成：（1）超悖论信息导航，包括主动采纳对立信息，聚焦于合成信息，和超越创生性三个要素；（2）超悖论情境考量，以谨慎精确和明辨时空为特征；（3）超悖论整合，由设计型整合与探索型整合组成。本文进而提出论述这三个维度之间互相依赖和互相增固机制的理论命题。本文不仅通过将具体的心智模式维度及其组成要素概念化而拓展了悖论研究，而且通过为悖论认知研究增添了动态、循环性过程，从而连接了悖论与认知视角的研究。